Ecotourism Policy Research Trends in Indonesia, Japan, and Australia - Saraswati Sisriany; Katsunori Furuya (Institut Pertanian Bogor (IPB University), 2020)
Numerous definitions and concepts regarding ecotourism lead to different implementations in ecotourism policies and systems. Identifying trends between countries provide valuable information for the development of inadequate ecotourism sites. This study aimed to understand the trends in ecotourism policies in Japan, Indonesia, and Australia by examining the bibliographic records of existing ecotourism policy research. These records were retrieved from the Scopus database and processed by using the scientometrics analysis. The results show the significant research trends of ecotourism policy in each country based on the co-occurrence of keywords were